2D Magnets: Intrinsic Magnetic Order of Chemically Exfoliated 2D Ruddlesden–Popper Organic–Inorganic Halide Perovskite Ultrathin Films (Small 52/2020). Issue 52 (28th December 2020) - Kim, Ki‐Yeon; Park, Garam; Cho, Jaehun; Kim, Joonwoo; Kim, June‐Seo; Jung, Jinyong; Park, Kwonjin; You, Chun‐Yeol; Oh, In‐Hwan
Abstract : In article number 2005445, Ki‐Yeon Kim, Garam Park, In‐Hwan Oh, and co‐workers synthesize few‐layered organic‐inorganic halide perovskite ultrathin films with their own intrinsic magnetic order by chemically exfoliating bulk compounds using a binary co‐solvent and spin coating technique. The atomically thin two‐dimensional organic‐inorganic halide perovskite magnets for spintronic applications are just around the corner.